Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 7 - Exponential Functions - 7.9 Hyperbolic Functions - Exercises - Page 384: 1


See the details below.

Work Step by Step

Since we have $$\sinh x= \frac{e^x-e^{-x}}{2}, \quad \cosh x= \frac{e^x-e^{-x}}{2}\cosh x= \frac{e^x+e^{-x}}{2}$$ Then we get $$\sinh -3= \frac{e^{-3}-e^{3}}{2}=-10.067, \quad \cosh x= \frac{e^{-3}+e^{3}}{2}\cosh x= 10.067$$ $$\sinh 0= \frac{e^{0}-e^{0}}{2}=0, \quad \cosh x= \frac{e^{0}+e^{0}}{2}\cosh x= 1 $$ $$\sinh 5= \frac{e^{5}-e^{-5}}{2}=74.20, \quad \cosh 5= \frac{e^{5}+e^{-5}}{2}\cosh x= 74.02$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.